Craniosynostosis affects the majority of mucopolysaccharidosis patients and can contribute to increased intracranial pressure. Issue 6 (6th August 2018) - Oussoren, Esmee; Mathijssen, Irene M. J.; Wagenmakers, Margreet; Verdijk, Rob M.; Bredero‐Boelhouwer, Hansje H.; van Veelen‐Vincent, Marie‐Lise C.; van der Meijden, Jan C.; van den Hout, Johanna M. P.; Ruijter, George J. G.; van der Ploeg, Ans T.; Langeveld, Mirjam
Abstract: Background: The mucopolysaccharidoses are multisystem lysosomal storage diseases characterized by extensive skeletal deformities, including skull abnormalities. The objective of this study was to determine the incidence of craniosynostosis in the different mucopolysaccharidosis (MPS) types and its clinical consequences. Methods: In a prospective cohort study spanning 10 years, skull imaging and clinical evaluations were performed in 47 MPS patients (type I, II, VI, and VII). A total of 215 radiographs of the skull were analyzed. The presence and type of craniosynostosis, the sutures involved, progression over time, skull shape, head circumference, fundoscopy, and ventriculoperitoneal shunt (VPS) placement data were evaluated. Results: Craniosynostosis of at least one suture was present in 77% of all 47 MPS patients (≤ 6 years of age in 40% of all patients). In 32% of all MPS patients, premature closure of all sutures was seen (≤ 6 years of age in 13% of all patients). All patients with early closure had a more severe MPS phenotype, both in the neuronopathic (MPS I, II) and non‐neuronopathic (MPS VI) patient groups. Because of symptomatic increased intracranial pressure (ICP), a VPS was placed in six patients, with craniosynostosis as a likely or certain causative factor for the increased pressure in four patients. One patient underwent cranial vault expansion because of severe craniosynostosis. Conclusions: Craniosynostosis occurs in the majority of MPS patients. Since the clinical consequences can be severe and surgical intervention is possible, skull growth and signs and symptoms of increased ICP should be monitored in both neuronopathic and non‐neuronopathic patients with MPS.